Anti-IgE: A treatment option in allergic rhinitis? - Pfaar, Oliver (Allergol Select, 2021)
Background: Allergic rhinitis (AR) is the most common IgE-mediated allergic disease. Multiple clinical trials have demonstrated promising results on the AR treatment with biologics, in particular with the use of omalizumab – an anti-IgE antibody. Omalizumab has also been established in the routine management of allergic asthma and chronic idiopathic urticaria. However, currently there is no approved license for the use of biologics in AR in Germany. Materials and methods: A systematic literature review has been completed including randomized controlled trials, meta-analyses, and reviews on the treatment of AR with omalizumab. Results: The systematic review demonstrates strong evidence supporting the use of omalizumab in the treatment of AR with regard to symptom control, safety profile, and management of comorbidities. Conclusion: Omalizumab is a good and safe option in the treatment of AR in terms of symptom control and the management of pre-existing comorbidities. Further clinical trials with other biologics in the management of AR are needed and are expected to follow soon.